Therapeutic Challenges and Emerging Treatment Targets for Pulmonary Hypertension in Left Heart Disease - Christelle Lteif; Ali Ataya; Julio D. Duarte (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Abstract Pulmonary hypertension (PH) attributable to left heart disease (LHD) is believed to be the most common form of PH and is strongly associated with increased mortality and morbidity in this patient population. Specific therapies for PH‐LHD have not yet been identified and the use of pulmonary artery hypertension‐targeted therapies in PH‐LHD are not recommended. Endothelin receptor antagonists, phosphodiesterase‐5 inhibitors, guanylate cyclase stimulators, and prostacyclins have all been studied in PH‐LHD with conflicting results. Understanding the mechanisms underlying PH‐LHD could potentially provide novel therapeutic targets. Fibrosis, oxidative stress, and metabolic syndrome have been proposed as pathophysiological components of PH‐LHD. Genetic associations have also been identified, offering additional mechanisms with biological plausibility. This review summarizes the evidence and challenges for treatment of PH‐LHD and focuses on underlying mechanisms on the horizon that could develop into potential therapeutic targets for this disease.